Synthesis and antibacterial activities of Ag-TiO2/ZIF-8 - Bao, Siqi; Sun, Shuanghui; Li, Lin; Xu, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, massive bacterial infections have led to human illness and death, reminding us of the urgent need to develop effective and long-lasting antimicrobial materials. In this paper, Ag-TiO2/ZIF-8 with good environmental friendliness and biological antibacterial activity was prepared by solvothermal method. The structure and morphology of the synthesized materials were characterized by XRD, FT-IR, SEM-EDS, TEM, XPS and BET. To investigate the antibacterial activity of the synthesized samples, Escherichia coli and Bacillus subtilis were used as target bacteria for experimental studies of zone of inhibition, bacterial growth curves, minimum bactericidal concentration and antibacterial durability. The results demonstrated that 20 wt.%Ag-TiO2/ZIF-8 had the best bacteriostatic effect on Escherichia coli and Bacillus subtilis under dark and UV conditions compared to TiO2 and ZIF-8. Under the same conditions, the diameter of the inhibition circle of 20 wt.% Ag-TiO2/ZIF-8 is 8.5-11.5 mm larger than that of its constituent material 4 wt.% Ag-TiO2, with more obvious antibacterial effect and better antibacterial performance. It is also proposed that the excellent antibacterial activity of Ag-TiO2/ZIF-8 is due to the synergistic effect of Ag-TiO2 and ZIF-8 under UV light. In addition, the prepared material has good stability and durability with effective antimicrobial activity for more than five months.